FOLKLORE AND MYTHOLOGICAL IMAGES OF THE HOMEWORK AND THE FORESTMAN IN THE ARTISTIC PLANE OF CHILDREN’S STORIES BY V. VYNNYCHENKA - Kobzej, Nataliya (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
The article analyses Volodymyr Vynnychenko’s children’s stories from the point of view of reproducing elements of the national code of Ukrainians recorded in folklore texts. Attention is focused on the author’s works "The Winds Are Blowing, the Winds Are Raging" and "Hey, who’s in the Woods, Call Out". It is established that the latter actively use folklore motifs, genres and images. They allow us to explain some of the folk traditions of our ancestors, to show the inseparability of the connection between the past and the present, and to recreate the flavour of the described era. It is determined that Ukrainian culture is characterised by beliefs in the existence of supernatural beings - witches, demons, devils, mermaids, sorcerers, werewolves - who can help or harm people. Vynnychenko borrows the images of a housekeeper and a forest man from folklore. The purpose of the study is to trace their transformation in these works and to find out their psycho-emotional impact on the characters. The historical and literary, comparative genetic, comparative typological and intertextual methods were used. Novelty. For the first time, the author analyses folklore and mythological characters in Vynnychenko’s children’s stories. It is proved that his forest man/Korchun underwent a significant literary transformation in the text. Parallels with typologically related images in world culture are drawn. The functions of folklore elements in the works are clarified: the composition of the stories is built around them, the characteristics of the main characters are revealed through the attitude to folklore images, and the author’s ideological and aesthetic concepts are realised. And in stressful situations associated with their appearance, the consciousness of small personalities is formed. The practical significance of the study lies in the fact that its results can be used in further research on literary and folklore correlations in V. Vynnychenko’s works.